2015
DOI: 10.1038/nbt.3155
|View full text |Cite
|
Sign up to set email alerts
|

Inducible in vivo genome editing with CRISPR-Cas9

Abstract: CRISPR/Cas9-based genome editing enables the rapid genetic manipulation of any genomic locus without the need for gene targeting by homologous recombination. Here we describe a conditional transgenic approach that allows temporal control of CRISPR/Cas9 activity for inducible genome editing in adult mice. We show that doxycycline-regulated Cas9 induction enables widespread gene disruption in multiple tissues and that limiting the duration of Cas9 expression or using a Cas9D10A (Cas9n) variant, can regulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
378
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(397 citation statements)
references
References 26 publications
10
378
0
3
Order By: Relevance
“…The discovery of CRISPR-Cas9 gene editing technology has also allowed for the development of genetic screens in organoid cultures and in vivo. However, this approach is dependent on having appropriate animal facilities and may be cost prohibitive 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of CRISPR-Cas9 gene editing technology has also allowed for the development of genetic screens in organoid cultures and in vivo. However, this approach is dependent on having appropriate animal facilities and may be cost prohibitive 20 .…”
Section: Discussionmentioning
confidence: 99%
“…These variants, including an intein-inactivated Cas9 system (Davis et al, 2015) and a small molecule-dimerized split Cas9 system (Zetsche et al, 2015b), have been shown to substantially improve genome editing specificity in mammalian cells compared with wild-type Cas9 by carefully controlling the temporal window within which active Cas9 is generated so that less active Cas9 is present after modification of the on-target loci is complete (Figure 2g,h). Similar systems, such as light-activated Cas9 variants (Nihongaki et al, 2015a;Hemphill et al, 2015;Jain et al, 2016), split Cas9 variants (Truong et al, 2015;Wright et al, 2015), small-molecule induction of Cas9 (Dow et al, 2015), and an engineered allosterically regulated Cas9 (Oakes et al, 2016) could also be used to reduce off-target genome editing following these same principles.…”
Section: Improving the Dna Specificity Of Crispr-based Agentsmentioning
confidence: 99%
“…In conjunction with this, we used the Cas9 nickase (Cas9 D10A ) for paired nicking of target sites, which has been demonstrated to significantly improve fidelity (3,5). The dual nickase approach also generates larger deletions after NHEJ (37,38) and may be more useful for generating null alleles. In our approach 4-hydroxytamoxifen (4-OH-T) and doxycycline (dox) regulate Cas9 D10A expression and nuclear localization (Fig.…”
Section: A Transposable Gfp Reporter To Assay Crispr Activitymentioning
confidence: 99%